Upaya Meningkatkan Hasil Belajar dengan Model Cooperative Learning Tipe Student Teams Achievement Division Kelas VII SMP Negeri 6 Rokan IV Koto - Zelmi Fitri Yeni (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The problem in this research is the low learning outcomes of class VII students at SMP Negeri 6 Rokan IV Koto in Mathematics subjects. To improve student learning outcomes, researchers applied the Student Teams Achievement Divisions (STAD) Cooperative Learning Model in Mathematics learning in class VII of SMP Negeri 6 Rokan IV Koto. This research is classroom action research, carried out in two cycles with a total of 23 students, each cycle consisting of four stages, namely planning action implementation, observation and reflection. From the results of the first cycle of action, 16 students got a score of more than 65 or 69.6% of the 23 students with an average score of 67.3, while 7 students got a score of less than 65 or 30.4% of the first cycle. 23 students. The results of the second cycle of action showed that 21 students got a score of more than 65 or 91.1% of 23 students with an average score of 83.3, while 2 students got a score of less than 65 or 8.9% of 23 students. student. Thus it can be concluded that the application of the Student Teams Achievement Divisions (STAD) Cooperative Learning Model can improve the learning outcomes of class VII students at SMP Negeri 6 Rokan IV Koto.